Green Reduction of Oxidized Graphite to Reduced Graphene Oxide Using Zygophyllum album L.f.: Comparative Adsorption Studies on p-nitrophenol - A. Fathy, Nady; R. Abd El-Latif, Rasha; M. M. Aboelenin, Reham; B. Khalil, Laila (Recent Innovations in Chemical Engineering, 2015)
Successfully studies were developed to produce reduced graphene oxide by green reduction of graphene oxide using environmentally-friendly reducing agents. Here for the first time, we report the green reduction of oxidized graphite (OG) to reduced graphene oxide (RGO) using the green plant called Zygophyllum album L.f. (Z. album) which revealed strong reducing activity. Techniques of TEM, Raman, FTIR and BET were carried out for characterization of both samples. Comparative adsorption studies for the removal of p-nitrophenol (PNP) using OG and RGO from aqueous solution in batch mode were studied. Impacting parameters such as pH of solution, adsorbent dose, agitation time, initial concentration of PNP and temperature were estimated. Kinetic studies confirmed that pseudo-second-order kinetic model successfully represented the adsorption process. Batch adsorption isotherms were examined by Langmuir, Freundlich and Florry-Hugins adsorption isotherms. It was found that the experimental data fitted well with the Langmuir model. At different pHs, the isotherms and thermodynamics of adsorption process were also measured, showing that PNP adsorption capacity was significantly pH dependent and endothermic. Maximum adsorption capacities occurred at pH 4 (i.e., 333.3 and 500 mg PNP per gram of OG and RGO, respectively). Therefore, the prepared adsorbents of OG and RGO could be used as potential adsorbents for removing the p-nitrophenol from wastewater.
Keywords: Green reduction